Strategi Kepala Sekolah Dalam Pengelolaan Vocational Life Skill Di Lembaga Pendidikan Islam (Studi Empiris Di MAN Kota Pasuruan) - Miftakhul Munir, Ina Mumtadzah (Al-Makrifat: jurnal kajian Islam, 2024)
The low quality of global education is closely related to social problems such as poverty, economic inequality and crime. Education is expected to be able to increase individual knowledge, skills and spirituality. Vocational skills, which focus on work and community service, are usually taught at the high school, vocational and MA levels. This research aims to describe the principal's strategy in managing vocational skills at MAN Pasuruan City and its impact.Using a qualitative approach and field study methods, this research reveals four main strategies of school principals: rational-empirical, normative-reducative, power-coercive, and alliance. Supporting factors include the role of the school principal, stakeholder support, student motivation, facilities, parental support, and collaboration with industry. The implications of this strategy increase students' independence, responsibility, courage to try new things, and Islamic character. However, challenges such as limited time, funds and facilities are still obstacles.Keywords:  Education, Vocational life skills.